Analysis of Communication and Compensation on Employee Job Satisfaction - Deddy Novie Citra Arta; Teguh Setiawan Wibowo; Pandu Adi Cakranegara; Marwan Hadi; Akhmad Nur Zaroni (PT Mattawang Mediatama Solution, 2022)
The purpose of this study was to analyze the effect of communication and compensation on employee job satisfaction. The research design used in this study used quantitative associative methods. Based on the results of data analysis that has been carried out on the first hypothesis (H1) which states that communication has a positive and significant effect on employee job satisfaction, the value of t count > t table is 13,684 > 1,666, testing the second hypothesis (H2) which states that compensation has a positive effect and significant on employee job satisfaction, the value of t count > t table is 12.665 > 1.666, which means that communication and compensation have a positive and significant effect on employee job satisfaction, while the R-square value obtained is 0.847 which states that the communication and compensation variables effect on employee job satisfaction by 84.70% and the remaining 15.30% influenced by other variables.